ARAHAN MITIGASI EROSI BERBASIS SPASIAL DI KAWASAN GUNUNG PADANG KOTA PADANG - Hary Febrianto; M.Iqbal Liayong Pratama; Nina Ismayani (Universitas Tamansiswa Padang, 2020)
This research is motivated by the level of land erosion hazard that occurs with the characteristic category of moderate and bad land erosion levels, the total erosion hazard that occurs is 669.65 ha, so it has an impact on land cover changes in the Mount Padang area which resulted in Edp exceeding its 4.2 ton limit. . The purpose of this study is to formulate spatial-based erosion mitigation directions in the Mount Padang area to the level of land erosion that occurs. The type of research used is R&D (Research and Development) through the stages of studying and understanding previous research, field surveys, and finally conducting literature studies in formulating spatial-based mitigation directions for the level of land erosion hazards that occur. The findings were obtained by the authors formulate spatial-based erosion mitigation directions in the form of spatial-based map-making actions in the Mount Padang area, as well as providing socialization to local communities in the Mount Padang area to be able to manage their lands properly.